2011
DOI: 10.1371/journal.pone.0024460
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism for Primordial Germ-Cell Migration Is Conserved between Japanese Eel and Zebrafish

Abstract: Primordial germ cells (PGCs) are segregated and specified from somatic cells during early development. These cells arise elsewhere and have to migrate across the embryo to reach developing gonadal precursors. Several molecules associated with PGC migration (i.e. dead-end, nanos1, and cxcr4) are highly conserved across phylum boundaries. However, since cell migration is a complicated process that is regulated spatially and temporally by multiple adaptors and signal effectors, the process is unlikely to be expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 32 publications
0
39
0
1
Order By: Relevance
“…Several genes associated with PGC development are conserved across fish species, even in those that are distantly related (Saito et al, 2006(Saito et al, , 2011. In this study, zebrafish PGCs were clearly visualized by co-injecting RFP-Asdnd 3′ UTR and GFP-nos3 3′ UTR mRNA.…”
Section: Discussionmentioning
confidence: 83%
“…Several genes associated with PGC development are conserved across fish species, even in those that are distantly related (Saito et al, 2006(Saito et al, , 2011. In this study, zebrafish PGCs were clearly visualized by co-injecting RFP-Asdnd 3′ UTR and GFP-nos3 3′ UTR mRNA.…”
Section: Discussionmentioning
confidence: 83%
“…Yamaha et al (2003) transplanted primordial germ cells (PGCs) of crucian carp (Carassius carassius) into embryos of the domesticated goldfish (C. auratus) and obtained donor-derived gametes from the matured "germline chimeras" (Yamaha et al 2003). Saito et al (2011) have shown that a single PGCs transplantation technique works even between marine and freshwater species. Okutsu et al (2007) have also produced germline chimeras by transplanting rainbow trout (Oncorhynchus mykiss) spermatogonia from adult testis into sterile hatched larvae of masu salmon (O. masou), and they clearly showed that the germline chimeras generated only gametes of the donor.…”
Section: Introductionmentioning
confidence: 99%
“…However, these aforementioned techniques have also drawbacks (see the review by Robles et al, submitted). To start with the case of PGCs transplantation as shown by Yamaha et al (2003) and Saito et al (2011), the manipulation must be performed in a short period during the embryonic stage. In addition, it is difficult to prepare PGCs in the amount appropriate for transplantation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations